PERANCANGAN ARSITEKTUR PERPUSTAKAAN DIGITAL UPH DAN RELEVANSI DSPACE SEBAGAI SOLUSI PENGELOLAAN DAN PENYEBARAN GREY LITERATURE - Hendryanto Djohan; Firman Ardiansyah; Janti G. Sudjana (Jurnal Pustakawan Indonesia, 2010)
Grey literature is one of library material types which can be accessed restrictedly by the patrons.The paradox is that grey literature contains very important information to support research andstudy. Therefore by building a digital library it is assumed both security and accessibility of users tothe grey literature content will be accomodated. Designing a digital library as an institutionalrepository for UPH by using the Zachman Framework will take a very important role in definingthe technical and normative features of an ideal digital library. In addition to, the exploration andmodification of DSpace by using Software Evolution method will also define the technical andnormative features of DSpace performance. The result of these will be compared to one another byusing a simple relevancy test procedure. The result are 90,625 % of relevancy degree on technicalfeatures and 95,7 % of relevancy degree on normative features. According to the result, it can beclaimed that a high relevancy degree is found between the pre-made architectural system of digitallibrary and the post-modification of DSpace program.Keywords: digital library, DSpace, grey literature, institutional repository, Zachman Framework.